Making the most of maps: GIS and topographical survey on the Island of Jarak - Fauzi, Rosmadi; Hussin, Azhar; A. Ghani, Azman; Ismail, Khaira (Malaysian Journal of Science, 2008)
The purpose of the GIS and topographic survey was to gather survey data on the natural, topographical and geological features of the island of Jarak, as well as its elevations. The topographic survey in this expedition fundamentally involved the production of maps and plans which were true to scale in the study area. The developed topographic maps will accurately represented details of both the natural and built environment on the island. Elevations data were taken with surveying equipment at several points on the island and plotted using GIS software. Through GIS analysis and field verification techniques, the dominant, natural and topographic features of the island have been identified and mapped. Tujuan penggunaan GIS dan tinjauan topografi dalam kajian ini ialah untuk mengumpul data ukur bagi ciri-ciri semulajadi, topografi dan geologi kepulauan Pulau Jarak serta aras ketinggiannya. Pada dasarnya, ukur topografi dalam ekspedisi ini melibatkan penghasilan peta dan pelan yang benar-benar tepat bagi kawasan kajian. Peta topografi yang terhasil akan mewakili kedua-dua perincian persekitaran semulajadi mahupun terbina sebagaimana yang terdapat di pulau tersebut. Data ketinggian dikumpul dengan menggunakan peralatan pengukuran di beberapa tempat pada pulau, dan seterusnya diplotkan dengan menggunakan perisian GIS. Menerusi analisis GIS dan teknik pengesahan di lapangan, ciri-ciri semulajadi dan topografi semasa yang nyata pada pulau tersebut telah dikenalpasti dan dipetakan.